When nonactivists care: Group efficacy mediates the effect of social identification and perceived instability on the legitimacy of collective action. (June 2019) - Jiménez-Moya, Gloria; Miranda, Daniel; Drury, John; Saavedra, Patricio; González, Roberto
In recent years, multiple social movements have emerged around the world. In addition, public surveys indicate the highest recorded levels of support for protest. In this context of acceptance of collective action, we examine the role of nonactivists in the perceived legitimacy of social movements, as this "passive" support can contribute to social change. Given that antecedents of legitimacy have been neglected in the literature, we carried out a survey ( N = 605) among a general sample of the population in Chile to shed light on this issue. We found that social identification with movements and perceived instability predicted the perceived legitimacy of protests by social movements, and that both variables had only indirect effects through group efficacy. This suggests that perceiving social movements as able to achieve success can lead nonactivists to perceive their actions as legitimate, highlighting the importance to movements of being seen to be effective.